Coexisting Coronary and Carotid Artery Disease: What We Did, What Happened - Güney,Mehmet Raşit (2022)
ABSTRACT Introduction: There is no complete consensus on the three surgical methods and long-term consequences for coexisting coronary and carotid artery disease. We retrospectively evaluated the surgical results in this high-risk group in our clinic for a decade. Methods: Between 2005 and 2015, 196 patients were treated for combined carotid and coronary artery disease. A total of 50 patients were operated on with the staged method, 40 of which had carotid endarterectomy (CEA) priority, and 10 had coronary artery bypass grafting (CABG) priority. CABG and CEA were simultaneously performed in 82 patients; and in 64 asymptomatic patients with unilateral carotid artery lesions and stenosis over 70%, only CABG was done (64 patients). Results were evaluated by uni-/multivariate analyses for perioperative, early, and late postoperative data. Results: In the staged group, interval between the operations was 2.82±0.74 months. Perioperative and early postoperative (30 days) parameters did not differ between groups (P-value < 0.05). Postoperative follow-up time was averaged 94.9±38.3 months. Postoperative events were examined in three groups as (A) deaths (all cause), (B) cardiovascular events (non-fatal myocardial infarction, recurrent angina, congestive heart failure, palpitation), and (C) fatal neurological events (amaurosis fugax, transient ischemic attack, and stroke). When group C events were excluded, event-free actuarial survival rates were similar in all three methods (P=0.740). Actuarial survival rate was significantly different when all events were included (P=0.027). Neurological events increased markedly between months 34 and 66 (P=0.004). Conclusion: Perioperative and early postoperative event-free survival rates were similar in all three methods. By the beginning of the 34th month, the only CABG group has been negatively separated due to neurological events. In the choice of methodology, “most threatened organ priority’’ was considered as clinical parameter.